Independent and joint associations of cardiorespiratory fitness and BMI with dementia risk: the Cooper Center Longitudinal Study - Laura F DeFina; David Leonard; Carolyn E Barlow; Galit Weinstein; Kerem Shuval; Kelley Pettee Gabriel; Jarett D Berry; Tal Gafni (BMJ Open)
Objective This study aimed to examine the association of midlife fitness and body mass index (BMI) with incident dementia later in life.Design and participants A cohort study of 6428 individuals (mean age 50.9±7.6 years) from the Cooper Center Longitudinal Study.Measures Cardiorespiratory fitness and BMI were assessed twice (1970–1999) during visits to the Cooper Clinic, a preventive medicine clinic in Dallas, Texas. These measures were examined as continuous and categorical variables. As continuous variables, fitness and BMI were examined at baseline (averaged of two examinations) and as absolute change between exams (mean time 2.1±1.8 years). Variables were categorised: unfit versus fit and normal versus overweight/obese. Medicare claims data were used to obtain all-cause dementia incidence (1999–2009). Mean follow-up between midlife examinations and Medicare surveillance was 15.7 ((SD=6.2) years. Multivariable models were used to assess the associations between fitness, BMI and dementia.Results During 40 773 person years of Medicare surveillance, 632 cases of dementia were identified. After controlling for BMI and covariates, each 1-metabolic equivalent increment in fitness was associated with 5% lower (HR 0.95; 95% CI 0.90 to 0.99) dementia risk. In comparison, after controlling for fitness and covariates, each 1 kg/m2 increment in BMI was associated with a 3.0% (HR 1.03; 95% CI 1.00 to 1.07) higher risk for dementia, yet without significance (p=0.051). Similar findings were observed when the exposures were categorised. Changes in fitness and BMI between examinations were not related to dementia. Jointly, participants who were unfit and overweight/obese had the highest (HR 2.28 95% CI 1.57 to 3.32) dementia risk compared with their fit and normal weight counterparts.Conclusion Lower midlife fitness is a risk marker for dementia irrespective of weight status. Being unfit coupled with overweight/obese status might increase one’s risk for dementia even further.